Ostracism, Self-Esteem, and Job Performance: When Do We Self-Verify and When Do We Self-Enhance? - Ferris, D. Lance; Lian, Huiwen; Brown, Douglas J.; Morrison, Rachel (Academy of Management Journal, 2015)
Self-esteem level has been positioned as a key mediating mechanism accounting for the effects of ostracism on behaviors, invoking the notion that individuals seek to verify their self-perceptions by behaving in a way that is consistent with those self-perceptions. However, evidence supporting the relation of ostracism and self-esteem level to behavioral outcomes has been mixed. We argue that such mixed effects arise because individuals may engage in behaviors alternately to verify their self-perceptions (suggesting a relation between self-esteem level and behavioral outcomes) or to self-enhance (suggesting no relation between self-esteem level and behavioral outcomes). Within this framing, the question becomes: When do we self-verify and when do we self-enhance? To that end, we position contingent self-esteem—or the extent to which individuals base their self-worth on outcomes in a particular domain—as a determining factor in whether we self-verify or self-enhance, and present a moderated mediation model to account for varying relations between ostracism and job performance. Our predictions regarding self-verification and self-enhancement motivation are fully supported across two field samples using multi-wave, multi-source study designs. Theoretical and practical implications for self-verification and self-enhancement motivation, as well as negative interpersonal behaviors at work, are discussed.